Sterol‐Targeted Laboratory Evolution Allows the Isolation of Thermotolerant and Respiratory‐Competent Clones of the Industrial Yeast Saccharomyces cerevisiae - Isabel‐Elena Sánchez‐Adriá; Jose A. Prieto; Gemma Sanmartín; Miguel Morard; Estéfani García‐Ríos; Francisco Estruch; Francisca Randez‐Gil (Microbial Biotechnology)
ABSTRACT Sterol composition plays a crucial role in determining the ability of yeast cells to withstand high temperatures, an essential trait in biotechnology. Using a targeted evolution strategy involving fluconazole (FCNZ), an inhibitor of the sterol biosynthesis pathway, and the immunosuppressant FK506, we aimed to enhance thermotolerance in an industrial baker's yeast population by modifying their sterol composition. This approach yielded six isolates capable of proliferating in liquid YPD with μmax values ranging from 0.072 to 0.236 h−1 at 41.5°C, a temperature that completely inhibits the growth of the parental strain. The clones were categorised into two groups based on their respiratory competence or deficiency, the latter associated with mtDNA loss, an event seemingly linked to FCNZ and heat tolerance. Genome sequencing and ploidy‐level analysis of all strains revealed aneuploidies, copy number variations (CNVs), and single nucleotide polymorphisms (SNPs). Notably, all evolved clones exhibited specific point mutations in MPM1 (P50S) and PDR1 (F749S). CRISPR‐Cas9 experiments confirmed the role of the pdr1F749S mutation in the FCNZ‐tolerance phenotype and demonstrated that Mpm1 is required for growth at high temperatures. However, no apparent heat tolerance benefit was observed from single or combined mutations in these genes, supporting the hypothesis that thermotolerance is mediated by multiple interacting mechanisms. In this context, all evolved clones exhibited altered sterol profiles, with differences observed between respiratory‐competent and ‐deficient strains. In conclusion, our experimental evolution generated thermotolerant and fully competent strains and identified factors that could influence fluconazole and heat growth.